# How do you rationalize the denominator and simplify #(sqrtx + 2sqrty)/(sqrtx - 2sqrty)#?

##### 1 Answer

Apr 3, 2016

#### Answer:

#### Explanation:

Multiply the fraction by the conjugate of its denominator.

#=(sqrtx+2sqrty)/(sqrtx-2sqrty)((sqrtx+2sqrty)/(sqrtx+2sqrty))#

In the denominator, we have what will become a difference of squares, which take the form:

#(a+b)(a-b)=a^2-b^2#

Here, we have

Thus, the fraction simplifies to be

#=(sqrtx+2sqrty)^2/(x-4y)#

This is a simplified answer. However, another perfectly acceptable way of presenting this would be to distribute the squared binomial as follows:

#=((sqrtx+2sqrty)(sqrtx+2sqrty))/(x-4y)=(x+4sqrt(xy)+4y)/(x-4y)#